Effectiveness of Septic Tanks Floating in Reducing COD, TSS, Temperature and pH of Waste Water Black - Marhama1, Agus Bintara Birawida1, Syamsuddin Toaha2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sanitation is the provision of facilities and services for disposal of human waste such as urine and feces.To reduce diseases arising from poor environmental sanitation, efficient technology that can be utilized bycommunities in coastal areas and small islands is one of the facilities what is needed for access to sanitationis a septic tank. This study aims to determine the sanitary conditions of communities in coastal areas andsmall islands and to determine the effectiveness of appropriate technology for floating septic tanks in coastalareas and small islands. The quality of wastewater that is important to know is Total Suspended Solid (TSS),Chemical Oxygen Demand (COD), Temperature and Hydrogen Power (pH).